Cyclic shear behavior of conventional and harmonic structure-designed Ti-25Nb-25Zr β-titanium alloy: Back-stress hardening and twinning inhibition. (September 2017) - Dirras, G.; Ueda, D.; Hocini, A.; Tingaud, D.; Ameyama, K.
Abstract: Spark plasma sintering was used to fabricate two Ti-25Zr-25Nb β-titanium alloys having a homogeneous microstructure and a so-called harmonic structure. Mechanical properties were evaluated by simple shear cyclic tests. The sample with homogeneous microstructure shows a large cumulative strain ~ 400% and a two-stage work-hardening associated with intense {332}〈113〉 mechanical twinning activity. Conversely, the harmonic-designed microstructure exhibits lesser cumulative strain ~ 200% but a higher cyclic strength. A complete twinning inhibition is observed. Indeed, the ultrafine-grained shell of the harmonic structure dispersed stress concentration. It accommodates plastic incompatibilities due to grain size difference by accumulating geometrically necessary dislocations at the shell/core vicinity. Graphical abstract: